PEMBAHARUAN SANKSI PAJAK SEBAGAI UPAYA MENGOPTIMALKAN PENERIMAAN NEGARA - Cahyadini, Amelia; Arta Atmaja, Budi; Oka Margana, Indra (Veritas et Justitia, 2017)
This paper examines about sanctions against the perpetrators of criminal acts in the field of taxation, where the position of criminal sanctions to be an interesting thing to see discussed up to now unknown tax ratio of Indonesia is still low when the tax It is the biggest contributor to the country's acceptance of Indonesia. The provisions of related criminal sanctions are also interesting when they are related to article 44B Act No. 28 of 2007 General provisions and Taxation Procedures in which the termination of the investigation can be carried out at the request of the Minister Finance to the Attorney General against Taxpayers who have tax debt that is not or less is paid in the form of administrative sanction plus a fine of four times the amount of tax that is not or less paid. The authors recommend several ideas that can be made of the Government in formulating the existing regulation back to fit the circumstances and conditions that occur and are able to meet the community's sense of fairness.